The Evocation of the Russian Empire Style in Serbian Architecture - Prosen, Milan (Actual Problems of Theory and History of Art, 2018)
This paper aims to highlight the acceptance of the Russian Empire style in the first half of the 20th century in Belgrade. The occurrence of the Empire style in Belgrade is unusual in relation to the time and spatial distance and the fact that the style was not present in Serbian cultural environment in the period of its flourishing during 19th century. The elements of the Empire style in public and private buildings are the evocation of the cultural memory of the Russian Empire, which was abolished at the time of the formation of capital of the Kingdom of SHS.This paper aims to highlight the acceptance of the Russian Empire style in the first half of the 20th century in Belgrade. The occurrence of the Empire style in Belgrade is unusual in relation to the time and spatial distance and the fact that the style was not present in Serbian cultural environment in the period of its flourishing during 19th century. The elements of the Empire style in public and private buildings are the evocation of the cultural memory of the Russian Empire, which was abolished at the time of the formation of capital of the Kingdom of SHS. This paper presents the research of the activities of Russian architects in Belgrade as a reflection of architectural, cultural, and political ties of St. Petersburg and the capital of the newly formed Kingdom of SHS/ Yugoslavia. The work traces the development of the architecture of Belgrade through the work of prominent emigrant builders, who arrived mainly from St. Petersburg, and who despite adaptation to already established stylistic currents in Belgrade, strongly emphasized their national diversity, evoking the imperial style of Alexander I that marked 19th-century buildings of Russian capital. The buildings erected in the Russian Empire style are rare for the Serbian environment. The significance of this architectural heritage is that it reflects an era and clearly stated Russian national identity, analogous to the representative buildings erected in St. Petersburg and Moscow in the 19th century. The evocation of the Russian Empire in Belgrade in the period 1920-1933 is also the last emanation of this style, which makes this phenomenon very important both for Russian and Serbian culture and also significant in the wider context of the world’s architectural heritage.